Complex Inflammation mRNA-Related Response in ALS Is Region Dependent - Sara Berjaoui; Mónica Povedano; Paula Garcia-Esparcia; Margarita Carmona; Ester Aso; Isidre Ferrer (Neural Plasticity)
Inflammatory changes are analyzed in the anterior spinal cord and frontal cortex area 8 in typical spinal-predominant ALS cases. Increased numbers of astrocytes and activated microglia are found in the anterior horn of the spinal cord and pyramidal tracts. Significant increased expression of TLR7, CTSS, and CTSC mRNA and a trend to increased expression of IL10RA, TGFB1, and TGFB2 are found in the anterior lumbar spinal cord in ALS cases compared to control cases, whereas C1QTNF7 and TNFRSF1A mRNA expression levels are significantly decreased. IL6 is significantly upregulated and IL1B shows a nonsignificant increased expression in frontal cortex area 8 in ALS cases. IL-6 immunoreactivity is found in scattered monocyte-derived macrophages/microglia and TNF-α in a few cells of unknown origin in ALS cases. Increased expression and abnormal distribution of IL-1β occurred in motor neurons of the lumbar spinal cord in ALS. Strong IL-10 immunoreactivity colocalizes with TDP-43-positive inclusions in motor neurons in ALS cases. The present observations show a complex participation of cytokines and mediators of the inflammatory response in ALS consistent with increased proinflammatory cytokines and sequestration of anti-inflammatory IL-10 in affected neurons.